2010
DOI: 10.1515/cclm.2010.161
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of coffee and green tea consumption with high-sensitivity C-reactive protein in Japanese men and women

Abstract: Coffee may be protective specifically against alcohol-induced hepatic inflammation. Further studies are warranted in different populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 30 publications
2
49
1
Order By: Relevance
“…Hs-CRP is synthesized predominantly in the liver and its serum levels may be more closely linked to the extent of hepatic inflammation (45). In a high-fat-diet (HFD)-induced NASH model in male Wistar rats, Vitaglione et al showed that coffee in drinking water significantly improved levels of glutathione and malondialdehyde (46).…”
Section: Discussionmentioning
confidence: 99%
“…Hs-CRP is synthesized predominantly in the liver and its serum levels may be more closely linked to the extent of hepatic inflammation (45). In a high-fat-diet (HFD)-induced NASH model in male Wistar rats, Vitaglione et al showed that coffee in drinking water significantly improved levels of glutathione and malondialdehyde (46).…”
Section: Discussionmentioning
confidence: 99%
“…5 An inverse association between coffee consumption and C-reactive protein concentrations has also been observed in Japanese populations. 17,18 In addition, habitual coffee consumption has been associated with higher insulin sensitivity. 3 Strengths of this study include its prospective and population-based design and the almost complete follow-up of study participants by linkage with population-based Swedish registers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in previous studies, sex-dependent associations of coffee consumption and biomarkers were detected (27,28). Male study participants were divided into 5 coffee consumption categories (.0 to ,2, 2 to ,3, 3 to ,4, 4 to ,5, and $5 cups/d).…”
Section: Methodsmentioning
confidence: 99%